The interplay of bedrock fractures and glacial erosion in defining the present-day land surface topography in mesoscopically isotropic crystalline rocks - Skyttä Pietari; Nordbäck Nicklas; Ojala Antti; Putkinen Niko; Aaltonen Ismo; Engström Jon; Mattila Jussi; Ovaskainen Nikolas (WILEY, 2025)
This paper addresses the effect of fractures within crystalline bedrock on glacial erosion processes in fast flowing hard bed glacier environments. In particular, we examine (i) whether the fracture type is critical for the capability of a glacier to erode the bedrock through quarrying/plucking processes and (ii) whether we can recognize specific fracture-controlled erosion signatures from bedrock surface morphologies. We conducted an investigation within the northern part of the angstrom land Islands, southern Finland, where the ice-flow direction (N-S) has remained constant through Late Pleistocene glaciations and where the bedrock is characterized by a lack of any mesoscopic anisotropies (such as foliation) and hence provides an optimal target to recognize the relationships between fractures and erosional morphologies. We characterized the fracture systems within the bedrock using both UAV-acquired orthophotographs and standard field approaches and extrapolated the results to larger scales using LiDAR-based digital elevation models. Our findings indicate that individual joints or shear fractures are associated with the development of minor vertical breaks along the bedrock surface. However, they do not provide sufficient mechanical weakness zones in the bedrock to allow effective glacial quarrying, even though their lengths can be relatively large (>50 m). By contrast, the linkage of several parallel shear fractures or the presence of larger faults with gouge-bearing cores and well-developed damage zones leads to localized disintegration of the rock material and the subsequent development of distinct topographic depressions along the bedrock surface. Consequently, the results allow predictions to be made about the bedrock features underlying the observed topographic signatures along the bedrock surface. Applied to the area of this investigation, abrasion associated with N-S-directed glacial flows is responsible for the N-S-oriented elongate but smooth fjord-like megagrooves, whereas the more abrupt topographic breaks were generated by quarrying controlled by sub-vertical, E-W-trending zones of localized brittle deformation.